Effect of nitrogen and phosphorus supply on growth, chlorophyll content and tissue composition of the macroalga Chaetomorpha linum (O.F. Müll), Kütz, in a Mediterranean Coastal Lagoon - Menéndez, Margarita; Herrera, Jorge; Comín, F. A. (Scientia Marina, 2002)
The effect of dissolved nutrients on growth, nutrient content and uptake rates of Chaetomorpha linum in a Mediterranean coastal lagoon (Tancada, Ebro delta, NE Spain) was studied in laboratory experiments. Water was enriched with distinct forms of nitrogen, such as nitrate or ammonium and phosphorus. Enrichment with N, P or with both nutrients resulted in a significant increase in the tissue content of these nutrients. N-enrichment was followed by an increase in chlorophyll content after 4 days of treatment, although the difference was only significant when nitrate was added without P. P-enrichment had no significant effect on chlorophyll content. In all the treatments an increase in biomass was obseved after 10 days. This increase was higher in the N+P treatments. In all the treatments the uptake rate was significantly higher when nutrients were added than in control jars. The uptake rate of N, as ammonium, and P were significantly higher when they were added alone while that of N as nitrate was higher in the N+P treatment. In the P-enriched cultures, the final P-content of macroalgal tissues was ten-fold that of the initial tissue concentrations, thereby indicating luxury P-uptake. Moreover, at the end of the incubation the N:P ratio increased to 80, showing that P rather than N was the limiting factor for C. linum in the Tancada lagoon. The relatively high availability of N is related to the N inputs from rice fields that surround the lagoon and to P binding in sediments.